Prevention of rib stress injury in rowers. What do we know and where do we need to go? - Thornton, J. S.; Vinther, A. (Sport-Orthopädie - Sport-Traumatologie, 2018)
Background: Rib pain is a common complaint among rowers and can lead to significant time loss from sport. Recent literature has emerged regarding rib stress injury (RSI) prevention and management. The aim of the present review was to update current knowledge regarding risk factors and injury mechanisms of RSI in rowers and suggest strategies for clinical application of this emerging evidence as well as suggest future areas of study. Material and methods: Existing literature on RSI risk factors and mechanisms, and on research methodology in overuse injuries in general, was reviewed. Results: Search results revealed several intrinsic and extrinsic factors related to rib stress and its response, including detrimental muscle loading of the ribs, low energy availability (LEA) and the potential influence of ergometer rowing. Conclusions: Emerging issues regarding risk factors and mechanisms in RSI may help inform clinical application and future research. There remains a pressing need for further studies regarding RSI aetiology and epidemiology to guide effective prevention strategies, particularly in subgroups such as para rowers and non-elites.